Deteksi Masker Wajah dengan Python OpenCV menggunakan Metode Haarcascade - Andi Nurazidin; Maulana Ibrahim; Anjani, Santi Aeri; Wahyu Ramadhan (Journal of Informatics and Computing, 2025)
Dust and viruses are reasons for someone to wear a mask. Because it can be the cause of diseases that attack the respiratory system. This condition is very important and needs to be watched out for. For this reason, someone uses a mask to protect himself, because wearing a mask is one way to reduce the risk of respiratory diseases. This makes the use of masks make digital image processing have good benefits, namely to detect the use of masks. With the existence of research on this system can find out the face of someone who uses a mask or not. The system was created using the Python and OpenCV programming languages with the Haarcascade method which is able to identify wearing medical masks, wearing non-medical masks, wearing masks incorrectly and people who are not wearing masks. Images or pictures and videos captured via a webcam, computer or laptop camera